2014
DOI: 10.1186/s12935-014-0092-x
|View full text |Cite
|
Sign up to set email alerts
|

Aged garlic extract protects against oxidative stress and renal changes in cisplatin-treated adult male rats

Abstract: BackgroundCisplatin (CP) is one of the effective anticancer drugs, but it causes many side effects. Aged garlic extract (AGE) is a natural herbal product used in management of many diseases.ObjectiveThis study aimed to investigate effect of AGE on CP-induced nephrotoxicity in rats.Material and methodsFour equal groups of adult male rats: control, AGE -treated (250 mg/kg, once oral dose/ 21days), CP-treated (7.5 mg/kg once i.p. on day 16th.), combined AGE and CP-treated were used. Body and kidneys weights of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 25 publications
5
39
0
Order By: Relevance
“…In this respect, our results show for the first time that periodontitis can reduce renal GSH levels caused by experimental periodontitis. Changes in GSH content were observed in injured kidneys by Nasr and Saleh (). Our results corroborated those authors’ findings, demonstrating the renal changes caused by experimental periodontitis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In this respect, our results show for the first time that periodontitis can reduce renal GSH levels caused by experimental periodontitis. Changes in GSH content were observed in injured kidneys by Nasr and Saleh (). Our results corroborated those authors’ findings, demonstrating the renal changes caused by experimental periodontitis.…”
Section: Discussionmentioning
confidence: 93%
“…In our model, we found increased levels of renal MDA in the periodontitis group in comparison with the control group, reported for the first time in the scientific literature. These higher MDA levels in the kidneys are common in cases of changed tissues (Nasr & Saleh, ).…”
Section: Discussionmentioning
confidence: 99%
“…37 The PAS results of this research were similar to another research that was done to study the effect of cisplatin (CP) on the kidney, revealed, weak positive PAS reaction in the brush border and basement membranes of the healthy PCT and DCT in CP-treated rats. 38 All the above mentioned apoptotic figures were confirmed by strong positive cytoplasmic and nuclear NF-kβ immunoreaction in the epithelial cells of the renal cortex compared with very weak Bcl2 immunoreaction. These results were approved statistically and by another study which concluded that the ROS activates NF-κB, which then ultimately leads to activation of ERK1/ERK2 pathway that lead to fibronectin expression.…”
Section: Discussionmentioning
confidence: 88%
“…However, the DCT of CP-treated rats showed apoptotic nuclear changes with fragmented nuclear envelop, thick basement membrane with few basal infoldings, small sized degenerated mitochondria, many lysosomes and cytoplasmic vacuoles. 38 The harmful effects of ACR were also approved by the biochemical results which showed high significant increase in the mean concentration of serum creatinine, BUN and LDH, and a high significant decrease in the mean concentration of serum albumin.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation